Designing a Data Literacy-Based Speaking Skills Assessment Instrument for High School Students - Faisal, Abdul Haris; Anshori, Dadang S.; Sastromiharjo, Andoyo; Mulyati, Yeti (LPPM Universitas Negeri Jakarta, 2024)
This study aims to develop a data literacy-based speaking skill assessment instrument for students at the high school level. Currently, speaking skills are one of the 21st century competencies that must be developed. Students of the 21st century have demands to master both written and oral communication competencies. In addition, data literacy skills are one of the new literacies that students must master as a complement to communication skills. This research uses a research and development method with the Plomp model which consists of five phases, namely the initial investigation phase, design phase, realisation phase, test, evaluation, and revision phase, and implementation phase. Data collection techniques were conducted by interview, document analysis, and questionnaire. The participants of this research involved teachers, assessment experts, linguistic experts, and speaking skill experts. The results of expert validation of the developed speaking skills assessment instrument obtained good results with a very feasible category so that the speaking skills assessment instrument product is feasible to be used to assess students' presentation skills in presenting scientific work at the high school level.